Real-Time Scheduling Architecture for Embedded Systems - Cayssials, Ricardo Luis (2013)
Industrial applications require meeting real-time specifications. Real-time systems are implemented using processors in order to execute real-time tasks. Temporal constraints must be supported by real-time operating systems or designing the application based on specific hardware resources. Previous approaches to real-time processors have implemented operating system functions in hardware and consequently they are designed to manage tasks’ periods rather than real-time. They cannot be used in a great deal of applications because they are based on restrictive models. This paper proposes the Hardware Real-Time Scheduling Architecture (HRTSA) that introduces an innovative methodology with which to efficiently manage time, events, priorities and tasks in an embedded hardware implementation. The HRTSA is described and realtime performance is evaluated